(untitled) (Spectrum, 2022)
This paper argues that William Shakespeare’s Macbeth can be read as pandemic literature. Though the tragedy is not about a plague, critics have already viewed it as a depiction of a claustrophobic ailing world with Macbeth and his accomplices running amok as agents of death and corruption. However, how the play actually speaks of real plagues and how it can be considered as pandemic literature have not been discussed adequately. Pandemic literature illustrates the ravages of plague as experienced, reminisced, and dreaded by the sufferers. The fictional world of Macbeth appears to be a plague-ridden world. The existence of deformed entities like the weird sisters, Malcolm’s familiarity with scrofula epidemic, Macbeth’s obsession towards the end with medicine, frequent appearances of doctors, and so on are some signs that the world of Macbeth was already going through a plague-like situation. The inhabitants of such a world often act frantically trying to escape death. They articulate stories of invisible horror and difficult survival, as if a plague had gripped them. The portrayal of Macbeth himself as an inhuman despot can serve as an indication that the tragedy is signaling to something beyond the rise and fall of a man – something terrible whose rampage is comparable to the devastation of a plague. This research asserts that Shakespeare’s Macbeth can be categorized under the pandemic literature genre. Spectrum, Volume 16, June 2021: 218-229